The Determination of Metabolic Activity of Freshly Isolated and Cryopreserved Human Fetal Liver Cells Using Alamar Blue Test - Petrenko, Yu. A.; Gorokhova, N. A.; Sandomirsky, B. P.; Petrenko, A. Yu. (Problems of Cryobiology and Cryomedicine, 2005)
The possibility of using the metabolic indicator Alamar Blue (AB) for fetal liver (FL) cells viability and proliferative activity assessment before and after cryopreservation was investigated. It is shown, that AB is the integral indicator of cells metabolic activity, which reflects the plasma membrane integrity as well as glycolysis intensity and respiratory chain activity in mitochondria. The inhibitory analysis of the AB reduction by human FL cells demonstrated that the glycolysis took the significant part in the total metabolic activity of cells of embryonic origin. The results demonstrate that the AB is a highly sensitive viability test for human FL cells and it could be used for the screening of cryopreservation protocol efficiency.